Tourist attractions of Ocaña and its region - Pacheco Carrascal, Marilce; Vergel Quintero, Damarys (Universidad Francisco de Paula Santander, 2015)
Based on the study of the Tourist Capacity of Ocaña and its Region, the information collected on the tourist attractions of Ocaña, La Playa de Belén, El Carmen and Ábrego in Norte de Santander is used as one of the elements that are part of the resources that allow the development of tourist activity, which boosts regional socioeconomic development. For this purpose, each of the towns under study was visited, where the tourist attractions were identified, many of them declared National, Departmental and Municipal Assets of Cultural Interest; evidencing that Ocaña and its region have a great tourist potential that would allow it to offer itself as a world class destination, but for this it requires the support and investment of both the public and private sectors and the support of educational institutions in the training of the necessary human resources to guarantee an excellent service.